2023
DOI: 10.1002/adma.202205377
|View full text |Cite
|
Sign up to set email alerts
|

Improving OFF‐State Bias‐Stress Stability in High‐Mobility Conjugated Polymer Transistors with an Antisolvent Treatment

Abstract: Conjugated polymer field‐effect transistors are emerging as an enabling technology for flexible electronics due to their excellent mechanical properties combined with sufficiently high charge‐carrier mobilities and compatibility with large‐area, low‐temperature processing. However, their electrical stability remains a concern. ON‐state (accumulation mode) bias‐stress instabilities in organic semiconductors have been widely studied, and multiple mitigation strategies have been suggested. In contrast, OFF‐state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Meanwhile, the red shift of the Soret band and Q bands reflected the formation of low-energy aggregates for TPAPP-Fe/Cu. As presented in X-ray diffraction (XRD) profiles (Figure D), TPAPP-Fe/Cu had a certain crystallinity, while TPAPP is amorphous, which suggested that the introduction of Fe 3+ and Cu 2+ endows the material with crystallinity that is conducive to the separation of carriers. Furthermore, the detailed elemental analysis was obtained from X-ray photoelectron spectroscopy (XPS) (Figure E). The C 1s peaks of TPAPP-Fe/Cu could be fitted into CC (283.84 eV) and CN (286.69 eV) (Figure F).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the red shift of the Soret band and Q bands reflected the formation of low-energy aggregates for TPAPP-Fe/Cu. As presented in X-ray diffraction (XRD) profiles (Figure D), TPAPP-Fe/Cu had a certain crystallinity, while TPAPP is amorphous, which suggested that the introduction of Fe 3+ and Cu 2+ endows the material with crystallinity that is conducive to the separation of carriers. Furthermore, the detailed elemental analysis was obtained from X-ray photoelectron spectroscopy (XPS) (Figure E). The C 1s peaks of TPAPP-Fe/Cu could be fitted into CC (283.84 eV) and CN (286.69 eV) (Figure F).…”
Section: Resultsmentioning
confidence: 99%
“…[ 42–44 ] Certain solvents can increase the degree of crystallinity of even weakly crystalline polymers, such as IDTBT, thus improving their bias stress stability. [ 45 ] We can use NMR to directly probe the presence of residual solvent in thin films by redissolving them in CDCl 3 after any processing steps (e.g., annealing).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, it is known from literature that solvents and solid‐state additives can improve OFET performance and stability. [ 24,40,41,45 ] Similarly, silane‐based SAM precursors are highly reactive towards water and can function as p‐type dopants [ 48 ] ; these features could both plausibly lead to stabilization effects in OFETs. We compared OFETs with pristine IDTBT films, i.e., with no intentional addition of solid‐state additives, and a Cytop‐M dielectric fabricated before and after the activated carbon replacement, to determine the effect of a contaminated glovebox atmosphere on device performance.…”
Section: Resultsmentioning
confidence: 99%
“…Sirringhaus et al removed water in the film from the void by inserting molecular additives to increase carrier mobility, stability, and homogeneity . They have also used an antisolvent processing method, which significantly improved the device performance and environmental stability of IDTBT films, and found that the enhanced crystallinity of the film in the effect of antisolvent hindered electron trapping and eliminated charge traps, allowing the mobility of ∼2 cm 2 V –1 s –1 . Geng et al have synthesized IDTBT polymers with an ultrahigh level of molecular weight (1049.6 kg mol –1 , M w ) and fabricated the corresponding polymer film of enhanced inner chain connectivity/entanglement with carrier mobility reaching 2.63 cm 2 V –1 s –1 .…”
Section: Introductionmentioning
confidence: 99%
“…28 They have also used an antisolvent processing method, which significantly improved the device performance and environmental stability of IDTBT films, and found that the enhanced crystallinity of the film in the effect of antisolvent hindered electron trapping and eliminated charge traps, allowing the mobility of ∼2 cm 2 V −1 s −1 . 29 Geng et al have synthesized IDTBT polymers with an ultrahigh level of molecular weight (1049.6 kg mol −1 , M w ) and fabricated the corresponding polymer film of enhanced inner chain connectivity/entanglement with carrier mobility reaching 2.63 cm 2 V −1 s −1 . 30 Even if the film aggregation state of semicrystalline polymers is generally enhanced through molecular design, 31−34 solvent engineering, 35−39 modulation of the film formation processing method, 40,41 and molecular additions, 42−45 developing an effective strategy to tune the aggregations of nearly amorphous IDTBT films to improve the carrier mobility of the film still remains challenging.…”
Section: ■ Introductionmentioning
confidence: 99%